Hanter la machine : reconquêtes de la conscience humaine dans le cyberpunk à la française - Simon Bréan (ReS Futurae, 2017)
The Cyberpunk movement provided us with many ways to question how the individual may cope with information technologies and cybernetics, which radically affect bodies and social interactions. Although no French cyberpunk movement really existed, many notable French works used and retooled its imagery and concepts. This paper aims at identifying an enduring peculiarity regarding the way “French Cyberpunk” deals with human-computer interactions : the importance of human consciousness for creating artificial intelligence.